Seaweed farming: A perspectives of genetic engineering and nano-technology application. Issue 4 (April 2023) - Khan, Nida; Sudhakar, K.; Mamat, R.
Abstract: In order to meet the growing demand for resources, there is a rising interest in macroalgae cultivation worldwide due to their potential as a source of food, fuel, and bio-products. However, large-scale and sustainable seaweed cultivation has been a persistent challenge. Specific fundamental issues need to be addressed to maximize the benefits of seaweed production. This article reviews a plan for transitioning to an environmentally sustainable aquaculture system incorporating non-toxic nanoparticles. It also provides an overview of genetic enhancement techniques for macroalgae species to realize their potential fully. Additionally, the article discusses the need for advanced tools and concepts to overcome the challenges in seaweed identification and cultivation and emphasizes the importance of a coordinated effort in fundamental and applied research using emerging technologies to ensure long-term practicality.